Genetic Background of Mesalamine-induced Fever and Diarrhea in Japanese Patients with Inflammatory Bowel Disease. Issue 1 (27th January 2021) - Suzuki, Kaoru; Kakuta, Yoichi; Naito, Takeo; Takagawa, Tetsuya; Hanai, Hiroyuki; Araki, Hiroshi; Sasaki, Yu; Sakuraba, Hirotake; Sasaki, Makoto; Hisamatsu, Tadakazu; Motoya, Satoshi; Matsumoto, Takayuki; et al.
Abstract: Background: Some patients with inflammatory bowel disease (IBD) who were under mesalamine treatment develop adverse reactions called "mesalamine allergy, " which includes high fever and worsening diarrhea. Currently, there is no method to predict mesalamine allergy. Pharmacogenomic approaches may help identify these patients. Here we analyzed the genetic background of mesalamine intolerance in the first genome-wide association study of Japanese patients with IBD. Methods: Two independent pharmacogenetic IBD cohorts were analyzed: the MENDEL (n = 1523; as a discovery set) and the Tohoku (n = 788; as a replication set) cohorts. Genome-wide association studies were performed in each population, followed by a meta-analysis. In addition, we constructed a polygenic risk score model and combined genetic and clinical factors to model mesalamine intolerance. Results: In the combined cohort, mesalamine-induced fever and/or diarrhea was significantly more frequent in ulcerative colitis vs Crohn's disease. The genome-wide association studies and meta-analysis identified one significant association between rs144384547 (upstream of RGS17 ) and mesalamine-induced fever and diarrhea ( P = 7.21e-09; odds ratio = 11.2). The estimated heritability of mesalamine allergy was 25.4%, suggesting a significant correlation with the genetic background. Furthermore, a polygenic risk score model was built to predict mesalamine allergy ( P = 2.95e-2). The combined genetic/clinical prediction model yielded a higher area under the curve than did the polygenic risk score or clinical model alone (area under the curve, 0.89; sensitivity, 71.4%; specificity, 90.8%). Conclusions: Mesalamine allergy was more common in ulcerative colitis than in Crohn's disease. We identified a novel genetic association with and developed a combined clinical/genetic model for this adverse event.